Quiet Revolution by SMEs in the midstream of value chains in developing regions: Wholesale markets, wholesalers, logistics, and processing - Reardon, Thomas; Liverpool-Tasie, Lenis Saweda O.; Minten, Bart (Springer, 2021)
Small and medium enterprises (SMEs) in the midstream (processors, wholesalers and wholesale markets, and logistics) segments of transforming value chains have proliferated rapidly over the past several decades in Africa, Asia, and Latin America. Their spread has been most rapid in the long transitional stage between the traditional and modern stages, when value chains grow long and developed with urbanization but are still fragmented, before consolidation. Most of Sub-Saharan Africa and South Asia, and parts of the other regions, are in that stage. The midstream SMEs in output and input value chains are important to overall food security (moving about 65% of food consumed in Africa and South Asia), and to employment, farmers, poor consumers, and the environment. The midstream of value chains is neglected in the national and international debates as the “missing middle.” We found that it is indeed not missing but rather hidden from the debate, hence “the hidden middle.” The midstream SMEs grow quickly and succeed where enabling conditions are present. Our main recommendations are to support the SMEs further growth through a focus on infrastructure investment, in particular on wholesale markets and roads, a reduction of policy-related constraints such as excessive red tape, and regulation for food safety and good commercial practices.